Integrated Reporting Disclosure Scores and Explanatory Factors: Case in Indonesia Context - Kartadjumena, Eriana; Devi Anna, Yane (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the company disclosure level based on the IIRC’s integrated reporting framework and also to explore its determining factors, namely the stand-alone sustainability report, sustainability index, and sustainability or corporate social responsibility committee. This research investigates the integrated reporting disclosure level of annual reports, websites, and sustainability reports from 87 companies’ websites in the Kompas 100 index. This study is a quantitative study and employs multivariate ordinary least squares regression to test the hypothesis. The results show that the corporate organizational overview, external environment, and governance have the highest scores of the integrated reporting disclosures index. On the other hand, the company outlook and business models had the lowest scores. This study shows that a stand-alone sustainability report has a significant influence on an integrated reporting disclosure score.